Natural internal thoracic-to-coronary artery collateral network. (February 2020) - Nagata, Tomoki; Hasegawa, Takao; Johno, Hiroyuki
We describe a rare case of three-vessel coronary disease in a 67-year-old man who had spontaneous communication between the left internal mammary artery and the left anterior descending artery. We decided to perform elective coronary artery bypass grafting. However, he died from sudden cardiac arrest before surgery.